Laser diagnostic method for plasma sheath potential mapping - Walsh, Sean P., author; Yalin, Azer P., advisor; Williams, John D., committee member; Rocca, Jorge G., committee member (Colorado State University. Libraries, 2016)
Electric propulsion systems are gaining popularity in the aerospace field as a viable option for long term positioning and thrusting applications. In particular, Hall thrusters have shown promise as the primary propulsion engine for space probes during interplanetary journeys. However, the interaction between propellant xenon ions and the ceramic channel wall continues to remain a complex issue. The most significant source of power loss in Hall thrusters is due to electron and ion currents through the sheath to the channel wall. A sheath is a region of high electric field that separates a plasma from a wall or surface in contact. Plasma electrons with enough energy to penetrate the sheath may result emission of a secondary electron from the wall. With significant secondary electron emission (SEE), the sheath voltage is reduced and so too is the electron retarding electric field. Therefore, a lower sheath voltage further increases the particle loss to the wall of a Hall thruster and leads to plasma cooling and lower efficiency. To further understand sheath dynamics, laser-induced fluorescence is employed to provide a non-invasive, in situ, and spatially resolved technique for measuring xenon ion velocity. By scanning the laser wavelength over an electronic transition of singly ionized xenon and collecting the resulting fluorescence, one can determine the ion velocity from the Doppler shifted absorption. Knowing the velocity at multiple points in the sheath, it can be converted to a relative electric potential profile which can reveal a lot about the plasma-wall interaction and the severity of SEE. The challenge of adequately measuring sheath potential profiles is optimizing the experiment to maximize the signal-to-noise ratio. A strong signal with low noise, enables high resolution measurements and increases the depth of measurement in the sheath, where the signal strength is lowest. Many improvements were made to reduce the background luminosity, increase the fluorescence intensity and collection efficiency, and optimize the signal processing equipment. Doing so has allowed for a spatial resolution of 60 microns and a maximum depth of measurement of ~2 mm depending on conditions. Sheaths surrounding common Hall thruster ceramics at various plasma conditions were measured in an attempt to determine the effect of SEE and a numerical analysis of the plasma-wall interactions was conducted to further understand the phenomena and compare against obtained data.